Tolerogenic Dendritic Cells for Regulatory T Cell Induction in Man - Raker, Verena K.; Domogalla, Matthias P.; Steinbrink, Kerstin (Frontiers in Immunology, 2015)
Dendritic cells are (DC) highly specialized professional antigen-presenting cells (APC) that regulate immune responses, maintaining the balance between tolerance and immunity. Mechanisms via which they can promote central and peripheral tolerance include clonal deletion, inhibition of memory T cell responses, T cell anergy and induction of regulatory T cells. These properties have led to the analysis of human tolerogenic DC as a therapeutic strategy for induction or re-establishment of tolerance. In the recent years, numerous protocols for the generation of human tolerogenic DC have been developed and their tolerogenic mechanisms, including induction of regulatory T cells, are relatively well understood. Phase I trials have been conducted in autoimmune disease, with results that emphasize the feasibility and safety of treatments with tolerogenic DC. Therefore, the scientific rationale for the use of tolerogenic DC therapy in the fields of transplantation medicine and allergic and autoimmune diseases is strong. This review will give an overview on efforts and protocols to generate human tolerogenic DC with focus on IL-10-modulated DC as inducers of regulatory T cells and discuss their clinical applications and challenges faced in further developing this form of immunotherapy.